Human Rights, Transitional Justice, and the Reconstruction of Political Order in Latin America - Carmody, Michelle Frances (2018)
In Argentina and elsewhere in Latin America, decades after the fall of authoritarian regimes in the 1970s, transitional justice has proven to be anything but transitional-it has become a cornerstone of state policy and a powerful tool of state formation. Contextualizing cultural and political shifts in Argentina after the 1976 military coup with comparisons to other countries in the Southern Cone, Michelle Frances Carmody argues that incorporating human rights practices into official policy became a way for state actors to both build the authority of the state and manage social conflict, a key aim of post-Cold War democracies. By examining the relationship between transitional justice and the Latin American political order, this book illuminates overlooked dimensions of state formation in the age of human rights.
1. Transitional Justice and the Construction of Democracy in an Age of Human Rights: An Introduction -- 2. Human Rights, Political Action, and the Precursors to Transitional Justice -- 3. The Official Story: Truth and Justice as Transition and Transformation -- 4. Reconciliation: Defining the Limits of Transitional Justice -- 5. Reconciliation Under Fire: New Contestations of Transitional Justice -- 6. (Re)forming the State: Recruiting the Dead and Revitalizing Transitional Justice -- 7. Nunca Más and State Making Beyond the Transition: A Conclusion.
Bibliography, index
Keywords: Historiography; World history; World politics; Latin American History; Memory Studies; Political History; World History, Global and Transnational History; Latin America -- History